2012
DOI: 10.1063/1.4766351
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of boron diffusion in an annealed Ta/CoFeB/MgO magnetic tunnel junction with standing-wave hard x-ray photoemission

Abstract: The CoFeB/MgO system shows promise as a magnetic tunnel junction with perpendicular magnetization and low critical current densities for spin-torque driven magnetization switching. The distribution of B after annealing is believed to be critical to performance. We have studied the distribution of B in a Ta/Co0.2Fe0.6B0.2/MgO sample annealed at 300 °C for 1 h with standing-wave hard x-ray photoemission spectroscopy (SW-HXPS). Comparing experimental rocking curve data to x-ray optical calculations indicates diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 21 publications
6
34
1
2
Order By: Relevance
“…This is consistent with earlier studies in which Ta is found to absorb boron from CoFeB. [64][65][66][67] There is also a possibility that the CoFeB layer intermixes with the neighboring HM layer, which will likely result in degradation of M S . However, for most cases, M S does not fall below that of bulk CoFeB, indicating that the degree of intermixing is not large.…”
Section: Perpendicular Magnetic Anisotropysupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with earlier studies in which Ta is found to absorb boron from CoFeB. [64][65][66][67] There is also a possibility that the CoFeB layer intermixes with the neighboring HM layer, which will likely result in degradation of M S . However, for most cases, M S does not fall below that of bulk CoFeB, indicating that the degree of intermixing is not large.…”
Section: Perpendicular Magnetic Anisotropysupporting
confidence: 80%
“…As the thickness of the dead layer is less than half a nanometer in most cases, it is di±-cult to identify the constituting elements. Recent studies 66 have shown that a thin TaB layer forms at the interface between Ta and CoFeB. It is yet to be con¯rmed whether the di®usion of boron is responsible for the formation of the dead layer for¯lms with other HM underlayers.…”
Section: Perpendicular Magnetic Anisotropymentioning
confidence: 99%
“…Tailoring the exciting X-ray wave field into a standing wave is a method for achieving greater depth sensitivity in photoemission, and it has been applied to a number of solid/solid interfaces [13][14][15][16][17] . In fact this method has also been applied previously in X-ray reflectivity and emission measurements on multilayer systems and at the solid-liquid interface 2,18 , but photoemission has the significant advantages of being more interface sensitive due to the shorter escape depths of electrons and of providing more direct chemical-state information from chemical shifts in core-level binding energies.…”
mentioning
confidence: 99%
“…[15][16][17][18] Meanwhile, the B atoms are pushed out of the CoFeB electrodes and then diffused into the MgO layers forming Mg-B-O spacer. [19][20][21][22][23] around (001) axis and compressing lattice slightly.…”
Section: -10mentioning
confidence: 99%